Tindak Pidana Terorisme dalam Perspektif Hukum Internasional dan Hukum Nasional - Isti Qomahnur Ananda; Nurpadila Nurpadila; Putri Rahmi Harahap; Aulia Rahmah Batubara (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
Terrorism is an extraordinary crime that threatens national and international security because it causes casualties, material losses, and disturbances to state stability. This research aims to analyze the definition of terrorism from the perspective of islamic, international, and national law, find out the history of the formation of anti-terrorism regulations in indonesia, and examine the form of sanctions against perpetrators of terrorism crimes. The research method used is normative juridical law research with a statutory approach, a case approach, and a comparative approach. Data was obtained through literature studies in the form of laws and regulations, books, journals, and other relevant legal sources. The results of the study show that in islamic law, terrorism can be categorized as jarīmah ḥirābah, which is an act that poses a threat and disturbance to public security. In international and national law, terrorism is understood as an act of violence or threat of violence aimed at creating widespread fear and disturbing public order. The establishment of anti-terrorism regulations in indonesia was influenced by the development of global terrorism, which then gave birth to law number 15 of 2003 and strengthened by law number 9 of 2013 concerning the prevention and eradication of terrorism financing. Sanctions against perpetrators include imprisonment, fines, asset blocking, asset forfeiture, and sanctions against the corporations involved. In addition to enforcement, the indonesian legal system also prioritizes prevention efforts through the supervision of financial transactions and inter-agency cooperation. Thus, the eradication of terrorism requires a comprehensive legal approach to ensure state security and the protection of the public.